Assessment of Bacteriological Quality of Drinking Water from Households of Sarvodaya Nagar, Lucknow, Uttar Pradesh, India - Shilpi Srivastava; Saurabh Kashyap; Ashish Rawat (Asian Journal of Medical Research, 2020)
Background: In the current scenario, the urbanization is happening at a faster pace and the economy is not able to match at par with urbanization, this In turn is causing problems of unavailability of safe and potable water along with proper sewage system, despecially in urban slums. As a result of the scenario many urban slums are still using poor quality pit latrines and even drawing water from nearby wells, water taps which are not complying with government norms. Space is also a big problem which is being faced by these slums, due to which there is a lack of enough spaces in the houses and nearby areas, therby causing overcrowding. Due to overcrowding, the space between houses, pit latrines, wells, taps and water bodies has decreased and thus the potential of contamination of water bodies by fecal microorganisms has increased drastically. Given the above knowledge, a study is much needed to estimate the presumptive and differential coliform count of water samples from the urban slum area in Lucknow. Subjects & Methods: A cross-sectional survey was conducted during the period of January to June 2019. Samples were collected from all the taps, hand pumps that were currently in use, along with potable water stored in households of Sarvodaya Nagar (an urban slum area), Lucknow and were processed in the Microbiology department of IIMS&R, Lucknow. Results: A total of 53(63%) samples were taken from Public supply, out of which 36(67. 9%) were found unsatisfactory and 17(32.0%) were intermediate, were found to be contaminated with Pseudomonas sp., E.coli, Thermotolerent E.coli, Klebsiella Spp. Citrobacter, Enterococcus and Pseudornonas Spp., E.coli, Thermotolerent E.coli, Klebsiella respectively. In the study more than half of the samples were taken from the Public water supply. Out of these about seventy percent were unsatisfactory and were found to be contaminated with Pseudomonas. Conclusion: The proper sanitation, regular treatment, supervision of water sources, arid regular bacteriological assessment of all water sources for drinking should be planned and conducted.